Changes of some soil chemical and microbiological characteristics in a long-term fertilization experiment in Hungary - Kátai, János; Tállai, Magdolna; Vágó, Imre; Balláné Kovács, Andrea (Acta Agraria Debreceniensis, 2018)
Agricultural management practices – directly or indirectly – influence soil properties. Fertilization rates and crop rotation can strongly affect soil pH, soil nutrient supply and soil organic matter content due to the changes of microbial processes. The objective of this study was to compare the effects of different fertilization doses in monoculture and tri-culture of maize (monoculture: only maize grown since 1983, tri-culture: it is a three-year crop rotation system: pea – winter wheat – maize) on selected soil characteristics. The long-term fertilization experiments were set up in 1983 in Eastern Hungary. These experiments are situated west of Debrecen in Hajdúság loess region, on calcareous chernozem (according to WRB: Chernozems). The test plant was maize (Zea mays L.). One-one pilot blocks were selected from monoculture and tri-culture of the long-term experiments. The observed soil samples were taken in the 30th year of the experiment, in 2013. The doses of NPK fertilizers increased parallel together, so the effects of N-, P- and K-fertilizers cannot be separated. With the increasing fertilizer doses, the soil pH has decreased in both crop production systems and, in parallel, the hydrolytic acidity has significantly increased. A close negative correlation was proved between the pHH2O, pHKCl and hydrolytic acidity. An increased nutrient content in soil was recorded in every NPK treatment and the available phosphorus and nitrate content increased in higher proportion than that of potassium. Of the measured parameters of C-and N-cycles, fertilization has mostly had a positive effect on the microbial activity of soils. Besides the effects of fertilizer doses, correlation were looked for between soil microbiological properties. Evaluating the ratios among the measured parameters (organic carbon and microbial biomass carbon, OC/MBC ratio; carbon-dioxide and microbial biomass carbon; CO2/MBC proportion), the fertilization rate seems to be favoured by the increase of amounts of organic compounds